THE EFFECTS OF SIMVASTATIN, ROSUVASTATIN, AND FENOFIBRATE ON THE BODY WEIGHT AND LIPID PROFILES OF FEMALE RATS TREATED WITH ORAL CONTRACEPTIVES AND A HIGH-FAT DIET - Dwi Anggara Putri; Yulia Yusrini Djabir; Muhammad Akbar Bahar; Gemini Alam; Latifah Rahman; Muhammad Aswad; Muhammad Aryadi Arsyad (Jurnal Kedokteran Hewan, 2022)
This study aimed to compare the effects of simvastatin, rosuvastatin, and fenofibrate therapies on the body weight and lipid profiles of the female rats receiving a combination of oral contraceptives (COC) and a high-fat diet (HFD). Twenty female Wistar rats (130-200 g) were divided equally into four groups. The rats received a standard diet for seven days, and their baseline lipid profiles were analyzed. All rats also received COC containing 15.1 µg/kg levonorgestrel/3.1 µg/kg estradiol with HFD for 60 days. Starting on day 31, the rats were given the respected treatment. The control group received the vehicle, whereas the others were treated with either simvastatin (2.1 mg/kg), rosuvastatin (0.5 mg/kg), or fenofibrate (8.2 mg/kg). Blood samples were taken on days 30 and 60. The results showed that the administration of COC+HFD and vehicle for 30 days increased the rats’ body weight and dyslipidemia, characterized by a significant decrease in Low-Density Lipoprotein (HDL) and an increase in total cholesterol (TC) and triglycerides (TG) levels (P0.05). Among the treatments, only fenofibrate was found to be able to prevent a significant weight gain in rats. Both fenofibrate and rosuvastatin inhibited a significant rise in TG and TC levels. Meanwhile, the simvastatin administration failed to do the same. Although statistically insignificant, all treatments increased rats’ HDL levels. Thus, it can be concluded fenofibrate was the most effective treatment among all in reducing weight gain and improving the lipid profile of dyslipidemic rats induced by oral contraceptives and a high-fat diet.